The subjective perception of the happiness of older adult residents in Colombia - Segura, Alejandra; Cardona, Doris; Segura, Angela; Robledo, Carlos Arturo; Muñoz, Diana Isabel (Frontiers in Medicine, 2023)
Introduction Happiness is understood as the perception of subjective well-being, it can be a quality, a result, or a state characterized by well-being or satisfaction that every person wants to achieve. In older adults, this satisfaction is a sum of lifelong achievements and triumphs; However, some factors influence this ideal. Objective Analyze demographic, family, social, personal, and health factors associated with the subjective perception of happiness in older adults, using data from a study conducted in five cities in Colombia, in order to make a theoretical contribution in the search for improvement of their physical, mental and social health. Materials and methods A quantitative, cross-sectional, analytical study was carried out, using primary source information, obtained with 2,506 surveys from voluntary participants aged 60 and over, who had no cognitive impairment, and who reside in urban areas but not in long-term centers. The variable happiness (classified as high or moderate/low) was used for: (1) A univariate explorative characterization of older adult, (2) a bivariate estimation of the relationships with the factors studied, and (3) a multivariate construction of profiles through multiple correspondences. Results 67.2% reported high happiness levels, with differences by city: Bucaramanga (81.6%), Pereira (74.7%), Santa Marta (67.4), Medellín (64%), and Pereira (48.7%). Happiness was explained by the absence of risk of depression and little hopelessness, strengthened psychological well-being, a perception of high quality of life, and living in a functional family. Conclusion This study provided an overview of possible factors that can be enhanced and strengthened with public policies (structural determinant), community empowerment, family strengthening (intermediate determinant), and educational programs (proximal determinant). These aspects are included in the essential functions of public health, in favor of mental and social health in older adults.